Towards Opioid-Free Elective Spine Surgery: A Prospective Cohort Study. (1st September 2019) - Sivaganesan, Ahilan; Wright, Amanda; Haid, Regis W; Mummaneni, Praveen V; Berkman, Richard
Abstract: INTRODUCTION: The opioid crisis is a national emergency. We conducted a prospective cohort study to determine whether elective spine surgery can be performed without any opioids whatsoever. METHODS: Every consecutive elective spine surgery performed by author R.A.B. between January 1st and December 31st of 2018 was included. For cohort A, between January and April 15th, opioids were minimized but PRN doses were given. For cohort B, between April 15th and December, the goal was to eliminate opioids altogether. Pain scores were collected at discharge, 1 wk, and 1-mo follow-up. Patient-reported outcomes (PRO) were collected at baseline and at 3 mo for lumbar procedures. Emergency room visits and readmissions were tracked. Student's t -tests were used to compare pain scores and PROs, and multivariate regression analyses were performed to understand drivers of opioid use. RESULTS: A total of 158 patients were included. In cohort A, 37.9% of patients took no opioids between PACU and 1 mo. Average pain scores were 5.2 in PACU and 2.5 at 1 mo. In cohort B, 86.7% took no opioids after PACU. Average pain scores were 4.2 in PACU and 2.5 at 1 mo. Both cohorts had equivalent improvements in PROs. Multivariate regression revealed that, adjusting for case mix differences, cohort B had lower odds of opioid use after PACU ( P < .0001). Moreover, preoperative opioid use is a driver of postoperative opioid use ( P = .02), whereas procedure type/invasiveness is not. CONCLUSION: We have shown that opioid-free spine surgery, including lumbar fusions, is feasible and effective. In all 87% of patients in our opioid-elimination cohort took no opioids from PACU until 1 mo after surgery, and 94% were taking none at the 1-mo visit. Pain scores and PROs were favorable. We have also shown that preoperative opioids are a driver of postoperative opioid use, however procedural invasiveness is not.